Analysis of Factors Influencing Students’ Insufficient English Vocabulary - Angelina, Alicia; Munir, Munir; Korompot, Chairil Anwar (State University of Makassar, 2025)
This study aims to identify the main factors contributing to the lack of English vocabulary among students. The research subjects consisted of ten students at SMAN 3 Makassar with poor English vocabulary. Using a qualitative descriptive method, data were collected through interviews and documentation. The study revealed that motivation plays a crucial role in mastering English vocabulary. Several factors hinder students' skill development, including low discipline in practice, lack of confidence, an unsupportive family environment, and inadequate support from the school. Among these, the primary obstacle is the lack of discipline in practicing, which is closely tied to motivation. This issue significantly affects students' ability to improve their English skills. Family and school support are also essential, as their absence contributes to the students’ struggles. Building motivation and encouraging consistent practice are key strategies to help students overcome these barriers and enhance their vocabulary mastery. These findings highlight the importance of fostering a supportive environment for students’ learning.Keywords: English Vocabulary, Insufficient Factors, Motivation.